DEVELOPMENT OF MULTI-HAZARD MAP DUE TO FLOOD AND TSUNAMI DISASTER IN COASTAL KULON PROGO, SPECIAL REGION OF YOGYAKARTA - Rianto, Ahmad
Yogyakarta International Airport (YIA), situated in Temon District, Kulon Progo Regency, Yogyakarta Special Region Province, serves as the primary airport for the Yogyakarta region. The area surrounding YIA is planned for development into an aerotropolis area, which is a metropolitan sub-region whose infrastructure, land use, and economy are centered on the airport. This development is anticipated to contribute to economic growth in Yogyakarta Special Region. However, YIA is situated between two river estuaries, the Bogowonto River and the Serang River, which renders it susceptible to flooding. Furthermore, the Kulon Progo coast is also at risk of a tsunami due to the Java Megathrust subduction. This study aims to assess the multi-hazard map due to floods and tsunamis in the Kulon Progo coast. The methodology employed included flood and tsunami disaster simulations and the development of multi-hazard maps using the Analytical Hierarchy Process (AHP). The results of both disaster simulations were then combined to develop a multi-hazard map. Multi-hazard analysis using AHP demonstrated that the weight of flood hazard in the YIA area was 0.614, while the weight of tsunami hazard was 0.386. The multi-hazard map developed from this analysis can be utilized as a tool to facilitate more effective and comprehensive disaster mitigation planning in the YIA area and its surrounding regions. It is anticipated that this multi-hazard map will provide benefits for further research and disaster mitigation planning in the Kulon Progo coastal area.